Collagen I and III Ratios and Tenacity of Rats' Muscle Injured and Treated with Platelet-Rich Plasma - Garcia, Thiago Alves; Tamura Ozaki, Guilherme Akio [UNESP]; Castoldi, Robson Chacon; Job, Aldo Eloizo [UNESP]; Trindade Camargo, Regina Celi [UNESP]; Silva Camargo Filho, Jose Carlos [UNESP]; Belangero, William Dias (Soc Chilena Anatomia, 2020)
Severe muscle injuries are common in accidents and have a delayed recovery of muscle integrity. In these cases, muscle suture surgery is the standard treatment. However, Platelet Rich Plasma (PRP), has been widely used in orthopedic injuries due to its growth factors. Thus, the objective of the study will be to analyze the association of suture and PRP techniques in the collagen and tenacity of the injured muscle. Were used seventy rats, divided into five groups: control (C), injury control (CI), injury and suture (IS), injury and PRP (IP), injury, suture, and PRP (ISP). Were sectioned approximately 50 % of the width and 100 % of the thickness of the gastrocnemius muscle. The homologous PRP was applied 24h after the injury. On the 7th day after the injury, the animals were euthanized and their muscles subjected to mechanical testing to measure tenacity or collagen analysis to calculate the ratio between type I and III collagen. The results show a significant decrease (p <0.05) in the values of the relationship between collagens in all injured groups (CI, IS, IP, ISP) compared to group C. In injured groups, the tenacity was significantly (p <0.05) reduced compared to the control group, with no observed difference between treatments and injured groups. The amount of collagen in the injured area has increased, but it did not affect the tenacity of the muscles, which was reduced.
Keywords: Muscle injury; Platelet-rich plasma; Suture; Collagen